Hubungan Motivasi Kerja Dan Pengembangan Karir Dengan Organizational Citizenship Behavior Pada Karyawan PT Anugrah Karya Prima - Hari Nugraha Putra; Sjahril Effendy; Dedi Sahputra (Mahesa Research Center, 2022)
This research aims to determine the correlation between work motivation and career development on organizational citizenship behavior (OCB) in employees of PT Anugrah Karya Prima Medan. The hypothesis proposed is that there is a positive and significant correlation between work motivation and career development on OCB in PT Anugrah Karya Prima Medan employees. The population in this research amounted to 62 people. Sampling technique is to use total sampling. Data collection methods are work motivation, career development, and OCB scales. Data analysis using multiple regression analysis model. The results of this research are: 1. There is a positive and significant correlation between work motivation and career development on OCB. This is indicated by the correlation coefficient (R) = 0.729 with p = 0.000 < 0.05. Based on the results of this research, the proposed hypothesis is accepted. 2. There is a positive and significant correlation between work motivation and OCB in employees of PT Anugrah Karya Prima Medan with the coefficient value obtained is 0.636 with a sig value. 0.000 < 0.05 and the proposed hypothesis is accepted with a strong correlation. 3. There is a positive and significant correlation between career development and OCB for employees of PT Anugrah Karya Prima Medan with the coefficient value obtained is 0.634 with a sig value. 0.000 < 0.05 and the proposed hypothesis is accepted with a strong correlation. The total effective contribution of the two independent variables (work motivation and career development) to OCB is 53.1%.